Survival Outcomes at Three Years After Primary vs Interval Debulking in Advanced Ovarian Cancer: A Retrospective Study from Hasan Sadikin Hospital (2021) - Alce Everdien; Andi Kurniadi; Dini Pusianawati; Aisyah Shofiatun Nisa; Dadang Hawari Subhan (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Objective: Ovarian cancer is the third most prevalent malignancy among women in Indonesia. The 5-year survival rate is approximately 49%, with 68% of patients diagnosed at an advanced stage. Standard treatment involves debulking surgery, which is categorized into primary debulking surgery (PDS) and interval debulking surgery (IDS). This study aims to compare the survival outcomes of ovarian cancer patients treated with PDS versus IDS at Dr. Hasan Sadikin General Hospital (RSHS) during 2021.Methods: A retrospective review of medical records was performed for ovarian cancer patients who underwent surgery at RSHS in 2021. Patients were classified according to the type of surgical management (PDS or IDS), and survival data were analyzed accordingly.Result: A total of 46 patients were included, with 38 undergoing PDS and 8 undergoing IDS. The mean overall survival was 34.1 months for the PDS group and 27.5 months for the IDS group. Bivariate analysis showed no significant difference in survival between the two groups (HR: 1.810, p = 0.341; 95% CI: 0.53–6.13). However, age (HR: 0.950, p = 0.014; 95% CI: 0.91–0.99) and progression-free survival duration (HR: 0.788, p = 0.0001; 95% CI: 0.71–0.86) were identified as significant prognostic factors for overall survival.Conclusion: The mean overall survival for patients undergoing primary debulking surgery (PDS) was higher than for those undergoing interval debulking surgery (IDS), although this difference was not statistically significant.Angka Kelangsungan Hidup Tiga Tahun Setelah Debulking Primer vs Interval pada Kanker Ovarium Stadium Lanjut: Sebuah Studi Retrospektif di RSUP Hasan Sadikin (2021)AbstrakTujuan: Kanker ovarium merupakan keganasan ketiga terbanyak pada wanita di Indonesia. Angka kelangsungan hidup 5 tahun sekira 49%, dengan 68% pasien datang pada stadium lanjut. Tatalaksana standar melibatkan operasi debulking yang diklasifikasikan menjadi operasi debulking primer (PDS) dan operasi debulking interval (IDS). Penelitian ini bertujuan untuk membandingkan hasil kelangsungan hidup pasien kanker ovarium yang diobati dengan PDS versus IDS di RSUP Dr. Hasan Sadikin (RSHS) selama tahun 2021.Metode: Sebuah studi retrospektif dilakukan melalui tinjauan rekam medis pasien kanker ovarium yang menjalani tatalaksana bedah di RSHS pada tahun 2021. Pasien dikategorikan berdasarkan jenis tatalaksana bedah (PDS atau IDS), dan data kelangsungan hidup dianalisis.Hasil: Sebanyak 46 subjek diikutsertakan, dengan 38 pasien menjalani PDS dan 8 pasien menjalani IDS. Rerata kelangsungan hidup keseluruhan adalah 34,1 bulan pada kelompok PDS dan 27,5 bulan pada kelompok IDS. Analisis bivariat tidak menunjukkan perbedaan signifikan dalam kelangsungan hidup antara kedua kelompok (HR: 1,810, p = 0,341; 95% CI: 0,53–6,13). Namun, usia (HR: 0,950, p = 0,014; 95% CI: 0,91–0,99) dan durasi kelangsungan hidup bebas progresi (HR: 0,788, p = 0,0001; 95% CI: 0,71–0,86) diidentifikasi sebagai faktor prognostik yang signifikan terhadap kelangsungan hidup keseluruhan.Kesimpulan: Rata-rata kelangsungan hidup keseluruhan pasien yang menjalani operasi debulking primer (PDS) lebih tinggi daripada rata-rata kelangsungan hidup keseluruhan pasien yang menjalani operasi debulking interval (IDS), meskipun tidak signifikan secara statistik.Kata kunci: Angka kelangsungan hidup; kanker ovarium; pembedahan debulking interval; pembedahan debulking primer